Enzymatic activity of avocado (persea americana) var. Fuerte during refrigerated storage - Liñan-Pérez, Jhoselyn (2021)
The aim of this study was to evaluate the effect of physical treatments (heat treatment at 45 ° C: TT), chemical (citric acid 1.0%: AC 1.0%; ascorbic acid 0.75%: AA 0, 75% and 1.0% sodium tripolyphosphate: 1.0% TPS), combined (0.2% citric acid and 45 ° C: 0.2% AC + TT) and a control treatment (C), in the inhibition of enzymatic browning, measured through the enzymatic activity (Δabsorbance/min) of Polyphenol Oxidase (PPO), in avocado tissue stored at refrigeration temperature (4 °C). The CIELAB color parameters (L*a*b*), ∆E*, ∆C* and the percentage of obscuration were evaluated. In addition, a sensory test was carried out with 50 consumers who evaluated the preference of the treated avocado samples. In general, the anti-browning treatments reduced the enzymatic activity of PPO where the sample treated with citric acid at 0.2% and 45 ° C obtained the best results in reducing the enzymatic activity and the color parameters.